2023
DOI: 10.14336/ad.2023.0312
|View full text |Cite
|
Sign up to set email alerts
|

Complications of COVID-19 on the Central Nervous System: Mechanisms and Potential Treatment for Easing Long COVID

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) invades human cells by binding to the angiotensin-converting-enzyme-2 (ACE-2) using a spike protein and leads to Coronavirus disease-2019 (COVID-19). COVID-19 primarily causes a respiratory infection that can lead to severe systemic inflammation. It is also common for some patients to develop significant neurological and psychiatric symptoms. The spread of SARS-CoV-2 to the CNS likely occurs through several pathways. Once spread in the CNS, many acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 151 publications
0
2
0
Order By: Relevance
“…EMR ( 5 ) not only inhibits caspase-1 (and other caspases) but may also inhibit the activity of the main SARS-CoV-2 protease as well as SARS-CoV-2 binding to the ACE-2 receptor. Such multi-target activity may prove useful in the treatment of infections caused by positive-strand RNA viruses besides SARS-CoV-2 [ 67 , 68 ].…”
Section: Caspase Inhibitorsmentioning
confidence: 99%
“…EMR ( 5 ) not only inhibits caspase-1 (and other caspases) but may also inhibit the activity of the main SARS-CoV-2 protease as well as SARS-CoV-2 binding to the ACE-2 receptor. Such multi-target activity may prove useful in the treatment of infections caused by positive-strand RNA viruses besides SARS-CoV-2 [ 67 , 68 ].…”
Section: Caspase Inhibitorsmentioning
confidence: 99%
“…Клиническое разнообразие течения COVID-19 характеризовалось целым спектром неврологических нарушений, многие из которых сохранялись в течение продолжительного времени после клинического стихания инфекционного процесса. Наиболее распространенными симптомами являлись: головная боль, миалгия, потеря обоняния и вкуса, нарушение сознания, психомоторное возбуждение, вялость, явления энцефалопатия и головокружение [1840]. Сообщается, что 95,6% врачей отмечали у своих больных COVID-19 по крайней мере один из неврологический симптомов [1841].…”
Section: наиболее частые варианты коморбидности острых респираторных ...unclassified
“…COVID-19 is primarily characterized by an acute respiratory infection with fever, fatigue, dry cough, myalgia, and dyspnea, with less typical symptoms being headache, dizziness, and abdominal pain [ 2 ]. Current treatments involve symptomatic care with antipyretics, oxygen therapy, antiviral drugs such as interferon alpha and remdesivir, and adequate hydration [ 3 ]. A recent study found that the discharge rate of COVID-19 patients was 52%, and the fatality rate was 5% [ 4 ].…”
Section: Introductionmentioning
confidence: 99%